KUALITAS SEMEN BEKU KAMBING PERANAKAN ETAWAH PADA PERMUKAAN NITROGEN CAIR DENGAN JARAK YANG BERBEDA (Frozen semen quality of pe goat in liquid nitrogen surface with different distance) - Revy Andryansyah; Teguh Sumarsono; Fachroerrozi Hoesni; Bayu Rosadi (JURNAL NUKLEUS PETERNAKAN, 2020)
The research was undertaken to study the effect of frozen semen distance from liquid nitrogen surface during handling on spermatozoa quality of PE goat. Thirty straws of PE goat frozen semen was allotted into six treatments i.e. T0 (control, straws submerged in liquid nitrogen), T1 to T5 based on distance of straws to liquid nitrogen surface were 5, 10, 15, 20, and 25 cm. Variables measured were motility, viability, and abnormality of spermatozoas. The results showed that PE goat frozen semen exposed in different distance to liquid nitrogen surface decreased (P<0.05) motily and viability of spermatozoas and had no effect (P>0.05) on abnormality of spermatozoas. The motily and viability was decreased in T4 and T5. In conlusion, exposing PE goat frozen semen from liquid nitrogen surface at 15 cm or less for 5 min maintain the quality of spermatozoas.